Efficacy of COVID convalescent plasma therapy in hospitalized moderate coronavirus disease 2019 patients - Irawan, Cosphiadi; Rumende, Cleopas Martin; Sukrisman, Lugyanti; Pitoyo, Ceva Wicaksono; Suwarto, Suhendro; Susilo, Adityo; Mulansari, Nadia Ayu; Harahap, Alvin Tagor; Priantono, Dimas; Syafitri, Ria; Chunaeni, Saptuti; Ritchie, Ni Ken (The Journal of Infection in Developing Countries, 2023)
Introduction: Covid Convalescent Plasma (CCP) failed to demonstrate its efficacy in severe and life-threatening coronavirus disease 2019 (COVID-19) cases. However, the role of CCP in hospitalized moderate cases is unclear. This study aims to examine the efficacy of administering CCP to hospitalized moderate coronavirus disease 2019 patients. Methodology: An open-label randomized controlled clinical trial design was used from November 2020 – August 2021 at two referral hospitals in Jakarta, Indonesia, and the primary outcome was mortality at 14 days. The secondary outcomes were mortality at 28 days, the time-to-discontinuation of supplemental oxygen, and the time-to-hospital discharge. Results: This study recruited 44 subjects, and the intervention arm consisted of 21 respondents who received CCP. The control arm consisted of 23 subjects who received standard-of-care treatment. All subjects survived during the fourteen-day follow-up period, and the 28-day mortality rate in the intervention group was lower than the control (4.8% vs 13.0%; p = 0.16, HR = 4.39 (95% CI = 0.45-42.71). There was no statistically significant difference in the time-to-discontinuation of supplemental oxygen and time-to-hospital discharge. During the total follow-up period (41 days), the mortality rate in the intervention group was also lower than the control (4.8% vs 17.4%, p = 0.13, HR = 5.47, 95% CI = 0.60–49.55). Conclusions: This study concluded that in hospitalized moderate COVID-19 patients, CCP did not reduce 14-day mortality compared to the control. Mortality during 28 days and total length of stay (41 days) were lower in the CCP group compared to the control, although they did not reach statistical significance.